2021
DOI: 10.1051/0004-6361/202141425
|View full text |Cite
|
Sign up to set email alerts
|

Electron conduction opacities at the transition between moderate and strong degeneracy: Uncertainties and impacts on stellar models

Abstract: Electron conduction opacities are one of the main physics inputs for the calculation of low- and intermediate-mass stellar models. A critical question considers how to devise a bridge when calculating both moderate and strong degeneracy, which are necessarily performed adopting different methods. The density-temperature regime at the boundary between moderate and strong degeneracy is, in fact, crucial for modelling the helium cores of red giant branch stars and the hydrogen-helium envelopes of white dwarfs. Pr… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 46 publications
0
17
0
Order By: Relevance
“…For each chemical composition, the higher stellar mass and the lowest luminosity level correspond to the predicted Zero Age Horizontal Branch (ZAHB) values (see, e.g., Pietrinferni et al 2013, and references therein). To account for possible uncertainties in the evolutionary luminosity prediction (see, e.g., Valle et al 2013;Cassisi et al 2021, and references therein), a slightly brighter (by 0.1 dex) luminosity level (than the ZAHB one) for the ZAHB stellar mass is also considered, while lower stellar mass (by about 10%) and still brighter models (0.2 dex more than the ZAHB level) were also computed for each Z and Y combination, in order to model possibly evolved RR Lyrae (see Marconi et al 2015, and references therein, for details). In particular, all the bolometric light curves of models with effective temperatures within the F or FO instability strip for the tabulated chemical compositions and masses have been transformed into the Rubin-LSST filters u LSST , g LSST , r LSST , i LSST , z LSST , and y LSST bands.…”
Section: Theoretical Light Curves In the Rubin-lsst Filtersmentioning
confidence: 99%
“…For each chemical composition, the higher stellar mass and the lowest luminosity level correspond to the predicted Zero Age Horizontal Branch (ZAHB) values (see, e.g., Pietrinferni et al 2013, and references therein). To account for possible uncertainties in the evolutionary luminosity prediction (see, e.g., Valle et al 2013;Cassisi et al 2021, and references therein), a slightly brighter (by 0.1 dex) luminosity level (than the ZAHB one) for the ZAHB stellar mass is also considered, while lower stellar mass (by about 10%) and still brighter models (0.2 dex more than the ZAHB level) were also computed for each Z and Y combination, in order to model possibly evolved RR Lyrae (see Marconi et al 2015, and references therein, for details). In particular, all the bolometric light curves of models with effective temperatures within the F or FO instability strip for the tabulated chemical compositions and masses have been transformed into the Rubin-LSST filters u LSST , g LSST , r LSST , i LSST , z LSST , and y LSST bands.…”
Section: Theoretical Light Curves In the Rubin-lsst Filtersmentioning
confidence: 99%
“…A key ingredient is the electron conductivity in the frontier between moderate and strong degeneracy. Cassisi et al, 2021 andSalaris et al, 2022 have computed two sets of models using the electron conductivities obtained by Cassisi et al, 2007 andby Blouin et al, 2020b and have found that models computed with the Blouin et al conductivities were predicting longer cooling times at bright luminosities and shorter cooling times at fainter luminosities as compared with the Cassisi et al…”
Section: The Evolution Of Single White Dwarfsmentioning
confidence: 99%
“…Therefore, the effect of conductive opacities becomes secondary in this context. Before ending this section, it is worth mentioning that recently Cassisi et al (2021) found that the uncertainty on conductive opacity could be much larger than 5%, mainly in the regime of weak level of electronic degeneration. In our case, their results could affect mainly the uncertainties estimated for metal poor stars (i.e.…”
Section: Radiative and Conductive Opacitiesmentioning
confidence: 99%
“…The theoretical uncertainties of the Tip luminosity has been discussed in several previous works. For the most recent we refer to Viaux et al (2013), Valle et al (2013a,c), Serenelli et al (2017) Straniero et al (2020) and Cassisi et al (2021). Some of these works focused on the effect on the predicted Tip luminosity (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation